National competition reveals common errors in target delineation among young clinicians in radiation therapy - Qingyu Huang; Xue Dou; Jing Liu; Rui Feng; Xiang Zhang; Jinbo Yue (BMC Medical Education)
Abstract Background Radiation therapy's efficacy hinges on accurate tumor and organ delineation, a task currently dependent on manual methods prone to high variability and error. To address this, we organized a national targeting competition to identify and rectify common targeting errors among young clinicians. Methods An annual national competition in China was conducted for clinicians under 40, focusing on various cancer types. Participants submitted delineation work for anonymous expert review. The competition assessed integration of multimodal imaging and accuracy in delineation across different tumor types, including central nervous system, head and neck, lung, esophageal, breast, abdominal, pelvic, urinary, gynecological, and lymphoma tumors. Results Involving 506 clinicians over three years, the competition revealed significant variability in target delineation practices. Enhanced CT was the predominant method for tumor localization. Key challenges included insufficient integration of multimodal imaging and inaccuracies in delineating lymph nodes, anatomical barriers, and tumor motion. The findings highlighted a disconnection between theoretical knowledge and clinical application. Conclusions The findings highlight the necessity of ongoing education and the standardization of training protocols for clinicians, especially for those in the early stages of their careers.